Decelerated mass loss of Hurd and Johnsons Glaciers, Livingston Island, Antarctic Peninsula - Navarro Valero, Francisco José; Jonsell, Ulf; Corcuera Labrado, María Isabel; Martín Español, Alba (Journal of Glaciology, 2013)
A new 10 year surface mass balance (SMB) record of Hurd and Johnsons Glaciers, Livingston Island, Antarctica, is presented and compared with earlier estimates on the basis of local and regional meteorological conditions and trends.Since Johnsons is a tidewater glacier, we also include a calving flux calculation to estimate its total mass balance. The average annual SMB over the 10 year observation period 2002–11 is –0.150.10 m w.e. for Hurd Glacier and 0.050.10 m w.e. for Johnsons Glacier. Adding the calving losses to the latter results in a total mass balance of –0.090.10 m w.e. There has been a deceleration of the mass losses of these glaciers from 1957–2000 to 2002–11, which have nearly halved for both glaciers. We attribute this decrease in the mass losses to a combination of increased accumulation in the region and decreased melt. The increased accumulation is attributed to larger precipitation associated with the recent deepening of the circumpolar pressure trough, while the melt decrease is associated with lower summer surface temperatures during the past decade.